2000
DOI: 10.1073/pnas.97.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence correlation spectroscopy reveals fast optical excitation-driven intramolecular dynamics of yellow fluorescent proteins

Abstract: Fast excitation-driven fluctuations in the fluorescence emission of yellow-shifted green fluorescent protein mutants T203Y and T203F, with S65G͞S72A, are discovered in the 10 ؊6 -10 ؊3 -s time range, by using fluorescence correlation spectroscopy at 10 ؊8 M. This intensity-dependent flickering is conspicuous at high pH, with rate constants independent of pH and viscosity with a minor temperature effect. The mean flicker rate increases linearly with excitation intensity for at least three decades, but the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
280
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(299 citation statements)
references
References 28 publications
19
280
0
Order By: Relevance
“…We compare our interpretation of the results further in the Supporting Information, with reference to fluorescence correlation spectroscopy (FCS) of Schwille et al (4), lowtemperature absorption spectroscopy of Creemers et al (3) and single-molecule optical switching by Beltram and colleagues (7,8). More recently Blum et al (40) have shown further heterogeneity in YFP fluorescence and have detected species that exhibit blue-and red-shifted emission compared with the dominant 527 nm emission.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We compare our interpretation of the results further in the Supporting Information, with reference to fluorescence correlation spectroscopy (FCS) of Schwille et al (4), lowtemperature absorption spectroscopy of Creemers et al (3) and single-molecule optical switching by Beltram and colleagues (7,8). More recently Blum et al (40) have shown further heterogeneity in YFP fluorescence and have detected species that exhibit blue-and red-shifted emission compared with the dominant 527 nm emission.…”
Section: Discussionmentioning
confidence: 69%
“…They have also attracted the attention of spectroscopists owing to their complex photochemistry (2)(3)(4)(5). In particular, those in the YFP class (i.e.…”
mentioning
confidence: 99%
“…Correlation analysis, on the other hand, provides quantitative information about the timescales of conformational fluctuations; however, its interpretation is often complicated by its strong model dependence, and by the presence of optical artifacts. [28] Probability distribution analysis (PDA) is a recently developed statistical tool for predicting the shapes of single-molecule fluorescence resonance energy transfer (smFRET) histograms, which allows the identification of single or multiple static molecular species within a single histogram. We used a generalized PDA method to predict the shapes of FRET histograms for molecules interconverting dynamically between multiple states.…”
Section: Introductionmentioning
confidence: 99%
“…Even at moderate intensities, the contrast C is constant and independent of further intensity increase. Such behaviour indicates light-driven cis-trans isomerization [29,30]. This is also true for the fluorinated proteins in this study; however, the absolute values of C and accordingly [B] differ (eq.2).…”
Section: Photostability Determinationmentioning
confidence: 65%